IMPLEMENTASI POLA MENGAJAR OIKODOMEO BERDASARKAN SURAT-SURAT PAULUS DI GEREJA BETHEL INDONESIA GUNUNG SARI SALATIGA TAHUN 2019 - Miranda Monika (JOURNAL of THEOLOGICAL STUDENTS, 2019)
Teacher is responsible for ensuring that students understand and comprehend every material that has been delivered, so that the goal of a teaching is achieved, namely to make what is taught to learn and change which includes three aspects, namely cognitive, affective, and psychomotor. So the demands of teachers who are implemented in the church today is the formation of creative teaching patterns and in accordance with the principles of Bible truth, one of which is the Oikodomeo teaching pattern based on Paul's letters for the ongoing learning process that answers the needs of the church. Oikodomeo's Teaching Pattern is a permanent structure in the teaching process that is broken down into sections with the aim of changing behavior by building, shaping and strengthening that is not bound by space or place and time. Based on this background, the researcher has the goal of wanting to know the level of implementation of the Oikodomeo teaching pattern at Bethel Indonesia Church in Gunung Sari Salatiga in 2019. In this study, researchers used a quantitative approach with descriptive methods, where data collection will be done by questionnaire or questionnaire. This study uses a Likert scale, with a range of scores from 1 to 5. This study is a population study, so do not use samples. The results of this study is the level of implementation of the Oikodomeo teaching pattern at Bethel Indonesia Church in Gunung Sari Salatiga in 2019 by 88% of the maximum value with a very maximum implementation value.